Global organized crime: the new empire of evil - Raine, Linnea P.; Cillufo, Frank J. (CSIS reports, 1994)
International organized crime and terrorism: from drug trafficking to nuclear threats / Louis Freeh--Global financial systems under assault: countering the $500 billion conspiracy / William McLucas, Patrick Leahy, Robert Rasor, and Jack Blum--Hacking through the cyberspace jungle / L. Dain Gary, Donn Parker, Scott Charney, and James Christy--Maintaining the security, integrity, and efficiency of our financial system in a global criminal market / Stanley E. Morris--The international black market: coping with drugs, thugs, and fissile materials / Carol Hallett, Rensselaer Lee, Oliver "Buck" Revell, and David Kay--The crime without borders: a British view / David Veness--Containing the new criminal Nomenklatura / Claire Sterling, Peter Grinenko, and Ronald Murphy--The varied and many risks of global organized crime: wrap-up--Trends in global organized crime: additional observations / Robert H. Kupperman--Global organized crime: threats to U.S. and international security / R. James Woolsey